Characteristics and variations of in vivo Schlemm's canal and collector channel microstructures in enhanced-depth imaging optical coherence tomography. Issue 6 (28th September 2016) - Li, Pengcheng; Butt, Anum; Chien, Jason L; Ghassibi, Mark P; Furlanetto, Rafael L; Netto, Camila F; Liu, Yiyi; Kirkland, Wendy; Liebmann, Jeffrey M; Ritch, Robert; Park, Sung Chul
Abstract : Background/aims: To characterise in vivo Schlemm's canal (SC) and collector channels (CC) microstructures using enhanced-depth imaging (EDI) optical coherence tomography (OCT). Methods: Serial horizontal EDI OCT B-scans (81 scans, 15×5° rectangle) were prospectively obtained in the nasal and temporal limbus. SC cross-sectional area (CSA) was measured by delineating its lumen in each B-scan. CCs connected to SC were counted. SC CSA and the number of CCs were compared between the nasal and temporal areas. Results: Eleven eyes (11 normal subjects) were included (mean age, 28±5 years). SC and CCs were clearly demarcated in EDI OCT B-scans with excellent repeatability and reproducibility (intraclass correlation coefficients, 0.830–0.886 and 0.793, respectively; all p<0.001). SC CSA varied considerably among subjects, ranging from 1664 to 6007 µm 2 (average, 3514±1235 µm 2 ), and among different regions of the same eye with coefficient of variation in each eye ranging from 23% to 46% (average, 32±7%). The number of CCs in the analysed area also varied considerably among subjects, ranging from 5 to 11 (average, 8.73±1.85). The mean SC CSA (3839±1402 µm 2 vs 3189±1209 µm 2 ; p=0.033) and number of CCs (5.5±1.4 vs 3.3±1.1; p=0.001) were significantly greater nasally than temporally. The mean SC CSA was significantly correlated with the number of CCs (r=0.635, p=0.036). Conclusions: High-quality images of the aqueous outflow pathway can be obtained with a clinical device, avoiding postacquisition processing. In vivo SC and CC microstructures vary considerably among individuals and regions. SC tends to be larger in regions with more CCs.